2018
DOI: 10.5530/jyp.2018.10.89
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Stability Testing of Nanoemulsion Lotion Containing Centella asiatica Extract

Abstract: Objective: Centella asiatica (Pegagan) contains asiaticoside for treatment of striae patients by increasing the synthesis of collagen. Asiaticoside has a large hydrophilic molecule (959.12 g/mol), causing difficulty in penetration through the skin. Nanoemulsion has small droplet size so that the active substance can be delivered into the skin layer. This study aims to formulate and test the stability of nanoemulsion lotion containing pegagan extract. Methods: Nanoemulsion containing pegagan extract formulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 8 publications
2
12
0
2
Order By: Relevance
“…The droplet size of the nanoemulsion is typically in the range 20 to 300 nm for an optimized penetration with topical application. The results of the optimized formula showed a globule size of 245 nm which was in agreement with previously published data which indicated that, the globular size for any transdermal and topically applied vesicular drug delivery system is preferred to be less than 300 nm in order to penetrate easily through skin layers [ 42 , 43 ].…”
Section: Resultssupporting
confidence: 89%
“…The droplet size of the nanoemulsion is typically in the range 20 to 300 nm for an optimized penetration with topical application. The results of the optimized formula showed a globule size of 245 nm which was in agreement with previously published data which indicated that, the globular size for any transdermal and topically applied vesicular drug delivery system is preferred to be less than 300 nm in order to penetrate easily through skin layers [ 42 , 43 ].…”
Section: Resultssupporting
confidence: 89%
“…The cycle process was repeated according to the desired particle size. From the experiment of Gotu kola extract nanoemulsion, researchers obtained an average particle size of 198.4 nm with PDI 0.329 and zeta-30.9 mV after using HPH with 600 bar at 8 cycles to reduce the particle sizes of nanoemulsion [37]. Akbas, Soyler and Oztop, 2018 studied capsicin nanoemulsion in chilies, had an average particle size of 65 nm using HPH method with 140 bars in 5 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…The rotation speed was 50 rpm, and the dissolution medium was 0.1N HCl with 1% tween 20 at 37 ± 0.5 °C (30) . Samples (5 ml) were withdrawn at a regular time intervals (5,10,15,20,30,40,50 and 60 min) from the dissolution medium and the samples then filtered by using through a 0.45 μm filter syringe and were analyzed by UV/Vis spectrophotometer at the λ max. of the drug (31) .…”
Section: In Vitro Drug Dissolution Studymentioning
confidence: 99%
“…NEs are thermodynamically stable systems, formed of particular concentrations of oil, Smix and DDW with no phase separation and no cracking or creaming. Small droplet size prevents any flocculation, enabling the system to remain dispersed with no separation (40) , as shown in table (3). Table 3.…”
Section: Lcdp Ne Characterization Thermodynamic Studymentioning
confidence: 99%